Harnessing Heritage: The Impact of Local Wisdom-Based Marketing on Social Enterprise Performance in Indonesia - Siti Alhamra Salqaura; Nasib Nasib (Journal of Consumer Sciences, 2025)
Background: To advance economic development and societal well-being, it is essential to conduct comprehensive research analyzing the social entrepreneurship’s effect on the performance of economic and social aspects, together with the principal factors influencing these outcomes. Purpose: This study seeks to improve the efficacy of social entrepreneurship by highlighting its contribution to economic and social progress. The study employs a marketing management approach that incorporates aspects of local wisdom, rooted in Indonesian society's religious and cultural values. Method: This study involved 350 social entrepreneurs from 20 provinces in Indonesia. The study employs a quantitative method approach, utilizing Structural Equation Modeling (SEM). Findings: Both religiosity-based entrepreneurial marketing (REM) and the entrepreneurial marketing mix (EMM) substantially affect social enterprise performance (SEP). EMM shows a positive, substantial correlation with SEP, whereas REM shows a negative, statistically significant effect. Moreover, REM does not substantially influence the link between market orientation and SEP. Likewise, market orientation (MO) exhibits no substantial direct impact on the social enterprise performance. Conclusions: This research finds that EMM has a favorable and significant influence on SEP, while MO does not significantly affect social enterprise performance. Instead of mediating, REM shows a large yet negative impact. These results highlight the complexity of integrating REM with MO strategies in SEP. Research implication: This research provides valuable insights for social entrepreneurs, governments, and academics on the strategic integration of local wisdom heritage in marketing to accelerate SEP in Indonesia.